Pathogenesis and Management of Macular Hole: Review of Current Advances - Guzel Bikbova; Toshiyuki Oshitari; Takayuki Baba; Shuichi Yamamoto; Keisuke Mori (Journal of Ophthalmology)
Macular hole has been believed to be a disorder of vitreomacular interface, which forms as a result of abnormal vitreous traction from incomplete vitreous detachment. However, our recent studies demonstrated that dynamic forces, caused by mobile posterior cortical vitreous with fluid currents, exist already at early stages of macular hole development. Therefore, in eyes with flexible vitreous, the contributions of tractional forces due to vitreous shrinkage are unlikely. These facts indicate that in the development of idiopathic macular holes, there is a greater contribution of dynamic forces than has been previously reported. This review also evaluates the recent findings in the assessment of the idiopathic macular holes and the recent therapeutic strategies for optimal management. Inner limiting membrane is considered to improve anatomical closure rate; however, it is still questionable if peeling is necessary in holes less than 250 µm. There are plenty of publications indicating that in the management of small and medium size hole (less than 400 µm), use of long-lasting gas and face-down position is not always required; however, it may be necessary for the treatment of large holes. Ocriplasmin and expansile gas had been reported to be successful for management of small- and medium-sized holes and vitreomacular attachment.